Talent Allocation and Post-Reform Growth in Central America - Sinha, Rishabh (World Bank E-Library Archive, 2020)
This paper examines the post-reform economic growth in three Central American economies - Costa Rica, El Salvador, and Panama. From 1995 to 2015, each economy witnessed phenomenal shifts in labor market participation and occupational distribution of women. If the innate talent for a job did not change differently across genders, the occupational changes suggest that many talented women in the mid-1990s were in professions that did not conform to their comparative advantage. The paper studies the evolution of the occupational distribution using a model of occupational choice in which three forces create frictions to efficient allocation - discrimination in labor markets, obstacles to human capital accumulation, and preferences (or social norms). The analysis shows that the underlying improvement in talent allocation over the past two decades had a quantitative impact on growth in Costa Rica and Panama. Decomposing the aggregate effects reveals that the gains were driven by declines in obstacles to human capital accumulation. In contrast, shifts in labor market discrimination created headwinds for expansion. The aggregate effects in El Salvador are relatively mild and noisy to the extent that the qualitative effect is difficult to pin down. Nonetheless, the analysis finds that the preference for market work has increased sharply in El Salvador for both genders and has proved to be a drag on growth